Impact of Active Listening Training on Counselling Effectiveness Among Counselling Practitioners in Ondo State, Nigeria - Ayorinde Emola Akinnusi (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This study investigated the impact of active listening training on counselling effectiveness among counselling practitioners in Ondo State, Nigeria. A quasi-experimental research design with pre-test and post-test measures was adopted.